Brand Awareness Sebagai Mediasi Pengaruh Live Streaming dan E-Wom Terhadap Purchase Decision Produk Npure pada Tiktok Shop - Desak Made Chintya Nirmala Dewi; I Gusti Ngurah Oka Ariwangsa; I Gusti Ayu Wirati Adriati; Ni Putu Nina Eka Lestari (Jurnal Riset Manajemen dan Akuntansi, 2026)
The technological shift in daily activities makes people tend to make purchases on social media, especially on TikTok Shop because of the live streaming and electronic word of mouth features. The purpose of this study is to determine the effect of live streaming and electronic word of mouth on purchasing decisions for NPURE products on the TikTok Shop application in Denpasar City. This study is included in quantitative research using a questionnaire method that will be given to 160 respondents who have been selected using purposive sampling techniques. Data were analyzed using Structural Equation Modeling (SEM-PLS) to test the relationship between variables. The results of this study indicate that live streaming has a positive and significant effect on purchasing decisions, e-wom also has a positive and significant effect on purchasing decisions, live streaming has a positive and significant effect on brand awareness, e-wom has a positive and significant effect on brand awareness, brand awareness has a positive and significant effect on purchasing decisions, brand awareness can mediate the effect of live streaming on purchasing decisions, and finally brand awareness also successfully mediates the effect of e-wom on purchasing decisions.